Structural Optimisation for Mass Estimation of Large-Aspect-Ratio Wings with Distributed Hybrid Propulsion - João Carvalho; Rauno Cavallaro; Andrea Cini (Engineering Proceedings)
The current commitment towards aviation climate neutrality and decarbonisation is boosting research programmes on disruptive aircraft configurations featuring sustainable powertrains and fuel-efficient airframes. This trend is pushing the design towards high-aspect-ratio wings made of lightweight structures housing distributed propulsion systems. Airframe preliminary sizing and mass estimation of non-conventional configurations, if performed using legacy methodologies based on experience, gathered with traditional configurations may result in non-optimised and non-viable designs. Therefore, a physics-based optimisation approach may allow more accurate sizing and airframe mass estimation. The methodology suggested in this paper is based on the automatic generation of a global finite element model to estimate the weight and determine a feasible material distribution for the wing box structure of a strut-braced wing configuration by means of size optimisation. Composite materials with defined stacking sequences were assigned to the wing components and structural weight minimised with the aim of offsetting the weight penalties associated with this non-conventional aircraft configuration. Preliminary results suggest that the composite strut-braced wing could achieve a weight reduction of up to 44% compared to a composite cantilever wing with equal aspect ratio of 20. The actual weight reduction is thought to be lower due to potential overestimation of the cantilever configuration.